Ciências Sociais e Ideologia: Uma análise do desenvolvimento das ciências sociais à luz do materialismo histórico-dialético - Carneiro, Bruna Beatriz Lemes (2024)
Social science as an autonomous discipline of knowledge developed in the mid-19th century amid profound political, economic, philosophical and social transformations. Its main precursors, such as Condorcet, Saint Simon, Comte and Durkheim, believed that the method of analysis and understanding of social phenomena came from the same assumptions established for the understanding of natural phenomena, which gave rise to the positivist conception of historical sciences and became remains the main theoretical-methodological framework for understanding social reality to this day. In contrast to the positivist conception of history, Marx and Engels, through their analyzes of social reality and the development of capitalist society, inaugurated a new method of understanding social reality, which came to be called by authors of the Marxist tradition as historical-dialectical materialism. Therefore, the first chapter is dedicated to understanding how social science takes on an ideological character with the development of historical processes and political, economic and social transformations, highlighting the substantial differences of those who are considered its precursors. The second chapter is dedicated to understanding the conception of historical dialectical materialism from the work The German Ideology of Marx and Engels, where the authors highlight the intimate relationship between conceptions of the world and the organization of social reality with the way how humanity produces its material life. In order to highlight the current nature of historical-dialectical materialism, the third chapter has as its main interlocutor István Mészáros, an important intellectual in the Marxist tradition who highlights the current nature of historical-dialectical materialism when thinking about the possibilities of social transformation through the concept of human formation. For the author, work and education have a dialectical relationship, being constitutive of a humanized and emancipatory formation, that is, essential for the formation of the social consciousness necessary for the transformation and overcoming of the contradictions that deepen in the era of late capitalism. The research is a bibliographical research and has historical-dialectic materialism as a theoretical-methodological reference.